THE EFFECT OF SERVICE QUALITY, BRAND IMAGE, AND PRICE ON PURCHASE DECISION OF PROYEK ISENG MURAL IN SURABAYA CITY - Pangestu Maulana Bramanti; J.E. Sutanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This research tittle “The Effect of Service Quality, Brand Image, and Price on Purchase Decision of Proyek Iseng Mural in Surabaya City” This research is based on the growth of creative economy sector in Indonesia. The creative economy itself that the researcher discuss in mural sector is part of painting art. Proyek Iseng is business that run in service field that was established in 2017 which is rooted from sub-sector of interior design and visual communication, that is mural. The purpose of this research is to identify the effect of service quality, brand image, and price on purchase decision of Proyek Iseng mural with service quality variable (X1), brand image (X2), and price (X3) on purchase decision (Y). This research is quantitative with the population of mural service users in Surabaya City that are unknown the number (infinite population). The sample of this research is 25 who have used Proyek Iseng mural service using purposive sampling technique. Data collection method of this research uses questionnaire and the technique of this research is Chi Square ( 2) by being using SPSS software. The result of this research indicates that service quality does not affect significant on Proyek Iseng mural purchase decision, brand image does not affect significant on Proyek Iseng mural purchase decision, and price does not affect significant on Proyek Iseng mural purchase decision.